The Brain monitoring with Information Technology (BrainIT) collaborative network: EC feasibility study results and future direction - Piper, Ian; Chambers, Iain; Citerio, Giuseppe; Enblad, Per; Gregson, Barbara; Howells, Tim; Kiening, Karl; Mattern, Julia; Nilsson, Pelle; Ragauskas, Arminas; Sahuquillo, Juan; Donald, Rob; et al. (Acta neurochirurgica, 2010)
The BrainIT group works collaboratively on developing standards for collection and analyses of data from brain-injured patients and to facilitate a more efficient infrastructure for assessing new health care technology with the primary objective of improving patient care. European Community (EC) funding supported meetings over a year to discuss and define a core dataset to be collected from patients with traumatic brain injury using IT-based methods. We now present the results of a subsequent EC-funded study with the aim of testing the feasibility of collecting this core dataset across a number of European sites and discuss the future direction of this research network.
Gesehen am 03.05.2023